Grafos ORTH[h, s, t] - Pinto, José Wilson Coura. (2018)
Intersection graphs are a topic that has attracted great interest from researchers in the area of graph theory since the 1960s. In this thesis we study the intersection graphs of subtrees of a tree. More precisely we will present results on the class of graphs ORTH[h, s, t]. The graphs that belong to this class are those that admit a representation by intersection of subtrees of a host tree, in which the maximum degree of the host tree is h, the maximum degree of any subtree is s, all leaves of the subtree are also leaves of the host tree and two vertices are adjacent in the graph if and only if their corresponding subtrees have at least t nodes in common and at least one of these nodes is a leaf. Results of representability, non-representability and complexity for classes ORTH[h, s, t] with the different values of the parameters h, s or t are present in this work.